An Interactive Market-Planning Procedure - Welch, Robert L. (Econometrica, 1976)
[A process which combines a planning procedure for the allocation of final products and a multilateral nonrecontracting trading process for allocating primary and intermediate goods is defined and shown to satisfy Malinvaud's criteria for evaluating planning procedures. Central processing costs are lower than in the Malinvaud procedure since the central planner only collects information on final products.]